THE IMPACT OF ENVIRONMENTAL POLICY IMPLEMENTATION AND CARBON TAX APPLICATION ON FOSSIL ENERGY CONSUMPTION AT PT SEMEN BATURAJA TBK - Suci Rahma Dani; Rum Hendarmin; Reny Aziatul Pebriani (JEA17: Jurnal Ekonomi Akuntansi, 2025)
This study aims to analyze the effect of environmental policy implementation and carbon tax adoption on fossil energy consumption at PT. Semen Baturaja Tbk. This research is motivated by the high dependence of the cement industry on fossil energy, which contributes to increased carbon emissions, thereby requiring environmental policies and fiscal instruments to control energy consumption. This study uses a quantitative method with a Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. Data were collected through questionnaires distributed to 83 employees working in units related to energy and environmental management. The results show that environmental policy implementation has a positive and significant effect on fossil energy consumption, with a path coefficient of 0.335, a t-statistic value of 3.209, and a p-value of 0.001. Carbon tax adoption also has a positive and significant effect on fossil energy consumption, with a path coefficient of 0.314, a t-statistic value of 3.022, and a p-value of 0.003. Furthermore, the R-Square value of 0.305 indicates that both variables explain 30.5% of the variation in fossil energy consumption. These findings indicate that environmental policy implementation and carbon tax adoption play an important role in controlling fossil energy consumption and supporting corporate sustainability.